2022
DOI: 10.7150/jca.68408
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of BUB1B Contributes to the Progression of Thyroid Carcinoma and Predicts Poor Outcomes for Patients

Abstract: Objective: This study aimed to clarify the function and potential mechanism of BUB1B in THCA. Methods: Expression of BUB1B in THCA was firstly determined, and its important prognostic value was then demonstrated. The potential mechanism was initially predicted by KEGG analysis. To explore the specific function of BUB1B in THCA, we used lentivirus infection to knock down the BUB1B, and then performed flow cytometry, colony formation, transwell, and wound-healing assays. Related protein expression was detected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Taken together, these results suggest that the TTK inhibitor may rescue the cells from the apoptotic effects of paclitaxel. BUB1B, BUB3, or TTK overexpression has no effect on the sensitivity of PANC-1 cells to nabpaclitaxel treatment Overexpression of the SAC gene has been observed in various cancers, including pancreatic, thyroid, prostate, and liver cancers [38][39][40][41] . Our study found that overexpression of the three SAC genes (BUB1B, TTK, and BUB3) does not significantly affect sensitivity to nab-abraxane.…”
Section: Clinical Correlation Of Low Sac Proteins With Poor Outcome I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results suggest that the TTK inhibitor may rescue the cells from the apoptotic effects of paclitaxel. BUB1B, BUB3, or TTK overexpression has no effect on the sensitivity of PANC-1 cells to nabpaclitaxel treatment Overexpression of the SAC gene has been observed in various cancers, including pancreatic, thyroid, prostate, and liver cancers [38][39][40][41] . Our study found that overexpression of the three SAC genes (BUB1B, TTK, and BUB3) does not significantly affect sensitivity to nab-abraxane.…”
Section: Clinical Correlation Of Low Sac Proteins With Poor Outcome I...mentioning
confidence: 99%
“…Overexpression of the SAC gene has been observed in various cancers, including pancreatic, thyroid, prostate, and liver cancers [38][39][40][41] . Our study found that overexpression of the three SAC genes (BUB1B, TTK, and BUB3) does not significantly affect sensitivity to nab-abraxane.…”
mentioning
confidence: 99%
“…In this research, we used the previous cDNA to conduct a qRT-PCR assay in Light Cycler 480II (Roche, Basel, Switzerland) using SYBR Green technology (Takara), and primer sequences were obtained from a primer bank. Primer sequences were from previous references (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and primer bank (https://pga.mgh.harvard.edu/primerbank/). In addition, 2 −Dct was used to normalize and simplify to generate a riskscore.…”
Section: Collection and Validation Of Clinical Samplesmentioning
confidence: 99%